Law enforcement within protected areas - Bruce Bryden (Pachyderm)
Only a summary of the presentation was published. Notes since elephant and rhino share much of the same habitat in southern Africa security and law enforcement face the same challenges. The Rhino and Elephant Management Security Committee whose membership comprises representatives and owners, and law enforcement and investigation officiers with the overall mission to promote the security of both these species in southern African is operational. Major training and anti-poaching operations began in Kruger in 1986, this seems to have contained poaching which has been low and sporadic except for the years 1981-1985.